If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4w + -1)(6 + -1w) = 0 Reorder the terms: (-1 + 4w)(6 + -1w) = 0 Multiply (-1 + 4w) * (6 + -1w) (-1(6 + -1w) + 4w * (6 + -1w)) = 0 ((6 * -1 + -1w * -1) + 4w * (6 + -1w)) = 0 ((-6 + 1w) + 4w * (6 + -1w)) = 0 (-6 + 1w + (6 * 4w + -1w * 4w)) = 0 (-6 + 1w + (24w + -4w2)) = 0 Combine like terms: 1w + 24w = 25w (-6 + 25w + -4w2) = 0 Solving -6 + 25w + -4w2 = 0 Solving for variable 'w'. Factor a trinomial. (-6 + w)(1 + -4w) = 0Subproblem 1
Set the factor '(-6 + w)' equal to zero and attempt to solve: Simplifying -6 + w = 0 Solving -6 + w = 0 Move all terms containing w to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + w = 0 + 6 Combine like terms: -6 + 6 = 0 0 + w = 0 + 6 w = 0 + 6 Combine like terms: 0 + 6 = 6 w = 6 Simplifying w = 6Subproblem 2
Set the factor '(1 + -4w)' equal to zero and attempt to solve: Simplifying 1 + -4w = 0 Solving 1 + -4w = 0 Move all terms containing w to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -4w = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -4w = 0 + -1 -4w = 0 + -1 Combine like terms: 0 + -1 = -1 -4w = -1 Divide each side by '-4'. w = 0.25 Simplifying w = 0.25Solution
w = {6, 0.25}
| 2x-3=+x+4 | | -99+2x=-110-x | | 5+x/-2=16 | | 69.1=(2)3.14r | | -9+x/-4=-22 | | X+2iny=0 | | 3x-4=4x+7 | | x+x+x-2=16 | | 4x-2(4x+11)=14 | | 3x-7(3x+18)=36 | | 34-3x=-22+x | | (x+1/3)+(x+2/7)=2 | | 2x+14=-25-x | | -5(8t)=2 | | x^2+(-4-3x)+24=0 | | 4x-4=x-7 | | (1/2)x-5=(3x/4) | | -5(11-3t)=6+-4 | | 1/3x+1/4=7 | | 1467x=45x | | 2x^2+5-10=0 | | 3y+5y+x=7y | | 5x+30=8x-9 | | 4/5/-3/2 | | (1/2)-(p/3)=(3/4) | | 6a^2+2a= | | 5a-30=90 | | 20=2y+x | | -14-14w=w+1 | | 6x-2x-3=20 | | 2(15x-20)=5(8x-6) | | -55/-3 |